'It's just houses': the role of community space in a new housing development in the digital era. (30th March 2019) - Jacklin-Jarvis, Carol; Cole, Marion
Abstract : This paper explores the role played by social media and physical community space in creating community identity in a new residential area. It argues that physical space still matters in a digital era, as social media tends to draw similar people together, rather than building bridges between diverse groups of residents. To build community identity that is both cohesive and inclusive, it is important that community space is available from early on in a building programme.